Results of a concurrent training protocol in muscle function and quality of life in the pediatric population with type 1 diabetes: a pilot study in public health - Phillip Foster; Erna Gálvez; Patricio Pinto; Eduardo Cifuentes-Silva; Sandra Mahecha-Matsudo; Mauricio Inostroza-Mondaca (Boletín Médico del Hospital Infantil de México)
Background: Type 1 diabetes mellitus (T1DM) prevalence has increased in prevalence worldwide. T1DM is characterized by negative changes in glycemic control (e.g., increased risk of hypoglycemia) and moreover negatively impacts the quality of life and muscle function of the pediatric population with the disease. Method: seven participants of the Hospital Dr. Exequiel González Cortés (age 11 [10-13] years, 4 male and 3 female) participated in a 12-week, twice-weekly concurrent training program plus continuous glucose monitoring (CGM). The participants underwent the following assessments: anthropometric measurements (weight, height, and BMI), glycemic control (Glycated hemoglobin [HbA1c], hypoglycemic events diaries, time in range, and glycemic diaries), muscle function (standing broad jump, prone plank, 10 maximum repetitions [10RM] squat, and chest press), quality of life (Kidscreen-27 questionnaire), and aerobic capacity (20 m shuttle run test). Statistical analysis used the Shapiro–Wilk test (normality), one-way Analysis of variance (differences between months), and paired t-test (pre-post differences). Results: The HbA1c increased (p = 0.047). Muscle function improved in standing broad jump (p = 0.03), prone plank (p = 0.01), 10RM squat (p = 0.03), and 10RM chest press (p = 0.01). Quality of life increased in physical function (p = 0.03) and total score (p = 0.01). The running distance in the 20 m shuttle run test increased (p = 0.01). Conclusion: The concurrent training program plus CGM is effective in improving quality of life, muscle function, and running capacity in the pediatric population with T1DM.